The Relationship of Health Education About Prebiotics with Maternal Knowledge in the Provision of Healthy and Nutritious Complementary Feeding - Enny Yuliaswati; Acih Suarsih; Rasmina Anggi Permatasari Sidabutar; Ketut Resmaniasih; Widya Nengsih (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Improper complementary feeding remains a major child health concern in Indonesia, particularly the limited utilization of prebiotics in complementary foods, despite their potential role in supporting infant gut health and immune function. Maternal knowledge regarding prebiotic-based complementary feeding is considered an important factor that may be influenced by health education provided by midwives. This study aimed to examine the association between midwife-led health education on prebiotic complementary feeding and maternal knowledge regarding healthy and nutritious complementary feeding practices. An analytical cross-sectional study was conducted in the working area of the Andalas Public Health Center, Padang. A total of 86 mothers with infants aged 6–24 months were recruited using purposive sampling. Data were collected using a structured questionnaire that had undergone validity and reliability testing. Univariate and bivariate analyses were performed using the chi-square test with a 95% confidence level. The findings showed that 54.7% of mothers had good knowledge, 29.1% had sufficient knowledge, and 16.2% had poor knowledge. In addition, 60.5% of respondents had received health education on prebiotic complementary feeding from midwives. A significant association was found between health education and maternal knowledge (p = 0.002), with mothers who received health education being 3.2 times more likely to have good knowledge than those who did not. These findings suggest that strengthening routine and structured health education programs delivered by midwives may improve maternal knowledge and promote appropriate prebiotic-based complementary feeding practices, thereby supporting optimal infant nutrition and health outcomes.